The effects of traditional and electronic word-of-mouth on destination image: A case of vacation tourists visiting Branson, Missouri - Koji Ishida; Lisa Slevitch; Katia Siamionava (Administrative Sciences, 2016)
The effects of integrated word-of-mouth (WOM), both traditional and electronic, on tourism products are yet to be fully investigated. The current study aims to assess the effects of and differences between traditional WOM and electronic WOM, between personal WOM and commercial WOM, and between positive and negative WOM on a destination image. Results of the study indicate that traditional WOM had a greater influence on destination image compared to electronic WOM. Personal traditional WOM had a greater influence on destination image compared to electronic personal WOM and commercial WOM. However, negative WOM exerted less influence on the destination's image compared to positive WOM while negative electronic WOM had a greater influence on destination image compared to negative traditional WOM.
Keywords: 350; destination image; electronic word-of-mouth; traditional word-of-mouth; word-of-mouth